Implementasi Model Pembelajaran Bahasa dan Sastra Indonesia Berbasis Proyek Berdiferensiasi di SMA 8 Ternate - Sasmayunita, Sasmayunita; Haerul, Haerul; Thahir, Asriani; Afriyanti, Riskha (EDUKASI, 2023)
The aim of the research is to improve the process and outcomes of students’ Indonesian language learning through differentiated learning. This research uses classroom action research methods. The research subjects were students of class XI IPS I SMA Negeri 8 Ternate City, totaling 34 students. The research was carried out in two cycles consisting of planning, implementation, observation and reflection stages. Data on the process of implementing differentiated learning was obtained through observation sheets of teacher and student activities. Data on student learning outcomes is obtained from learning outcomes tests. The results of the research show that there has been an increase in the process of implementing differentiated learning from cycle 1 to cycle 2. Based on an assessment of the performance indicators for the success of student learning activities, data was obtained that in cycle 1 the good category was 50%, the category was fair, the category was 20%, and the poor category was 30%. In cycle 2, there was an increase in the success of student learning activities as seen from the achievement of the good category to 85%, the fair category 10% and the poor category 5%. From the results of the assessment of teacher performance indicators in cycle 1, it can be seen that a score of 68 was achieved in the poor category. In cycle 2, there was an increase in teacher performance which was seen from achieving a score of 90 in the very good category. From the results of the analysis of the research data, it can be concluded that the implementation of differentiated learning in Indonesian language learning can improve the learning process and outcomes.